MCQs and EMQs in surgery - Datta, Pradip K.; Bulstrode, C. J. K.; Praveen, B. V. (London : Hodder Arnold, 2010)
This book assists readers in their preparation for examinations and tests their knowledge of the principles and practice of surgery as outlined within 'Bailey & Love'. Sub-divided into 13 subject-specific sections, it provides a comprehensive coverage of the surgical curriculum as well as the core learning points outlined in 'Bailey & Love'.
Includes index.
Keywords: Surgery; Surgery